Influence of non‐metallic fraction of printed circuit boards waste on recycled polyvinyl chloride from waste wires. Issue 2 (30th July 2021) - Grigorescu, Ramona Marina; Ghioca, Paul; Iancu, Lorena; David, Madalina Elena; Ion, Rodica‐Mariana; Nicolae, Cristian‐Andi; Gabor, Raluca Augusta; Radu, Elena Ruxandra; Ganciarov, Mihaela; Spurcaciu, Bogdan; Alexandrescu, Elvira; Ciuprina, Florin
Abstract: Recycling of electric and electronic equipment is an emerging global issue in order to decrease the high amount of waste deposited on landfill or incinerated, and thus reducing the environmental pollution. Different strategies of eliminating this waste can be applied. In this paper, the non‐metallic fraction of printed circuit boards, due to the contained amount of glass fiber and rigid epoxy matrix, are considered suitable for valorization as reinforcing filler for polyvinyl chloride recovered from the insulation of equipment cables. The composites containing up to 30% filler are characterized in terms of structural, morphological, thermal, dielectric, mechanical and dynamic‐mechanical properties. Physical interactions are established between the components. Good homogeneity of composites at small dosages of filler is proven, and thus the mechanical and dynamic‐mechanical properties present increased or unchanged values compared with the polymeric matrix. At higher amounts of waste powder, some defects and agglomerates are observed and correlated with decreased values of the main tensile characteristics. Based on the physical‐mechanical and dielectric characterization, the paper shows that reinforced recycled polyvinyl chloride composites with 15%–20% non‐metallic fraction of printed circuit boards waste present suitable properties for reuse the polymer in different technical applications, mainly as insulating technical materials. Abstract :